Tajhin Sora dalam Tradisi Asyura - SAM, Achmad Al-Muhajir; Ubaidillah, Ubaidillah; Habibi, Erfan; Alfatani, Ifan Ali (Proceedings of Annual Conference for Muslim Scholars, 2025)
The current inquiry examines Bubur Suro (locally known as Tajhin Sora in Madura), an integral element of the Ashura tradition within the Bondowoso community. Beyond its physical form as a culinary dish, this tradition functions as a complex cultural artifact imbued with symbolic, historical, and social dimensions. This article aims to uncover the symbolic constructions, historical meanings, and social functions of Tajhin Sora in the context of the Islamic New Year. Utilizing a qualitative approach, the investigation gathered data through participant observation of rituals in East Java, in-depth interviews with cultural and religious leaders, and a comprehensive literature review. The findings reveal that Tajhin Sora serves as a material symbol of gratitude and spiritual victory, with historical narratives tracing back to the era of Prophet Noah. Socially, the ritual acts as a catalyst for social cohesion, intergenerational value transmission, and the reinforcement of Bondowoso’s cultural identity. The present analysis concludes that Tajhin Sora is a profound "living tradition" that continuously reproduces religious and socio-cultural values amidst modern shifts. Ultimately, the preservation of this tradition demonstrates the resilience of local culture in maintaining fundamental meanings within a contemporary framework